Matrix metalloproteinase-13 mediated degradation of hyaluronic acid-based matrices orchestrates stem cell engraftment through vascular integration. (May 2016) - Jha, Amit K.; Tharp, Kevin M.; Browne, Shane; Ye, Jianqin; Stahl, Andreas; Yeghiazarians, Yerem; Healy, Kevin E.
Abstract: A critical design parameter for the function of synthetic extracellular matrices is to synchronize the gradual cell-mediated degradation of the matrix with the endogenous secretion of natural extracellular matrix (ECM) (e.g., creeping substitution). In hyaluronic acid (HyA)-based hydrogel matrices, we have investigated the effects of peptide crosslinkers with different matrix metalloproteinases (MMP) sensitivities on network degradation and neovascularization in vivo . The HyA hydrogel matrices consisted of cell adhesive peptides, heparin for both the presentation of exogenous and sequestration of endogenously synthesized growth factors, and MMP cleavable peptide linkages (i.e., QPQGLAK, GPLGMHGK, and GPLGLSLGK). Sca1 + /CD45 − /CD34 + /CD44 + cardiac progenitor cells (CPCs) cultured in the matrices with the slowly degradable QPQGLAK hydrogels supported the highest production of MMP-2, MMP-9, MMP-13, VEGF165, and a range of angiogenesis related proteins. Hydrogels with QPQGLAK crosslinks supported prolonged retention of these proteins via heparin within the matrix, stimulating rapid vascular development, and anastomosis with the host vasculature when implanted in the murine hindlimb.